2019
DOI: 10.1155/2019/9752623
|View full text |Cite
|
Sign up to set email alerts
|

Study on Distribution Characteristics and Displacement Mechanism of Microscopic Residual Oil in Heterogeneous Low Permeability Reservoirs

Abstract: In order to explore the development methods suitable for heterogeneous low permeability reservoirs and study the distribution characteristics of residual oil, photoetched glass and artificial core models with three permeability ratios of 1, 6, and 9 were prepared in this research. Three displacement schemes including polymeric surfactant flooding, polymeric surfactant with binary flooding, and binary flooding were designed at the same expenses to obtain the displacement mechanism of various residual oil satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The residual oil in the small pores was mainly in the cluster and column forms while the residual oil in the membrane and column forms was mainly distributed in the large pores, with a small amount of the residual oil in form of islets, as shown in Figures 7A, C. Clustered residual oil continuously distributed in the small pores was the main form of residual oil distribution after water flooding (Fang et al, 2019).…”
Section: Stability Of Pickering Emulsions Stabilized By Fe 3 O 4 @Pda...mentioning
confidence: 88%
“…The residual oil in the small pores was mainly in the cluster and column forms while the residual oil in the membrane and column forms was mainly distributed in the large pores, with a small amount of the residual oil in form of islets, as shown in Figures 7A, C. Clustered residual oil continuously distributed in the small pores was the main form of residual oil distribution after water flooding (Fang et al, 2019).…”
Section: Stability Of Pickering Emulsions Stabilized By Fe 3 O 4 @Pda...mentioning
confidence: 88%
“…On the contrary, the microscopic visualization model could intuitively characterize the microscopic seepage mechanism of oil and gas. At present, the visualization models include an etched-glass and digital model from advanced imaging devices. Yun et al (2020) established a glass-based micromodel to represent the carbonates and revealed the surfactant-assisted oil recovery mechanism . Song et al (2020) studied the effect of different CO 2 injection rates on CO 2 saturation and mobility using a two-dimensional homogeneous model .…”
Section: Introductionmentioning
confidence: 99%